Evidence of underlying structural similarities of amorphous materials - Akihiko Hirata; Kengo Nishio; Masayuki Okugawa; Ryusuke Nakamura (Communications Materials)
Abstract Amorphous metal oxides are generally thought to be structurally different from metallic glasses because of the different types of bonding, such as ionic, metallic, and covalent. While amorphous metal oxides consist of metal atoms surrounded by oxygen atoms, metallic glasses resemble the dense random packing (DRP) of hard spheres. However, a theory suggests that the two different classes of materials have underlying structural similarities. Here, using angstrom-beam electron diffraction (ABED) and the polyhedron code, we provide experimental support for the theory by presenting evidence that the Hf sublattice in amorphous HfO2 contains atomic clusters dominated by pentagonal bipyramids, DRP’s key structural feature. We further observed remarkable similarities between the Hf sublattice and Zr80Pt20 metallic glass, together with distinct differences from amorphous Si and SiO2, which have open tetrahedral-bond-network structures. These findings pave the way for a deeper understanding of the universality of glass structures and their connection to material properties.